1947
DOI: 10.1021/ja01196a004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Decomposition of Hydrogen Peroxide Solutions with Manganese Dioxide. II

Abstract: Vol. 69 nese between colloid and solution, Tests B-l and B-2 were made. These were identical in all respects with A-l and A-2, except that radioactive manganese was used throughout. The results are reported in Table II.Radioactivity Center for aid in planning the radioactivity studies. SummaryA study has been made of the catalytic decomposition of hydrogen peroxide with oxides of manganese, formed in situ from permanganate or manganous salts and alkali. The use of radioactive tracers indicates that catalysis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
1

Year Published

1957
1957
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 0 publications
1
28
0
1
Order By: Relevance
“…The authors suggested that the significant enamel Ca loss was due to the high potential of concentrated HP to cause dental demineralization. The low stability of highly concentrated peroxides and the fast peroxide degradation reaction may lead to less interaction of the peroxide with the enamel structure 28 , causing the same alteration when using low or high concentrations, as observed in this study. Al-Salelhi et al 6 investigated the effect of 24 h non-stop 3%, 10% or 30% HP concentration on mineral loss and found increased ion release with increasing HP concentration.…”
Section: Discussionsupporting
confidence: 62%
“…The authors suggested that the significant enamel Ca loss was due to the high potential of concentrated HP to cause dental demineralization. The low stability of highly concentrated peroxides and the fast peroxide degradation reaction may lead to less interaction of the peroxide with the enamel structure 28 , causing the same alteration when using low or high concentrations, as observed in this study. Al-Salelhi et al 6 investigated the effect of 24 h non-stop 3%, 10% or 30% HP concentration on mineral loss and found increased ion release with increasing HP concentration.…”
Section: Discussionsupporting
confidence: 62%
“…(6)], which hints at the possibility of a reaction mechanism consisting of the combination of Equations (5) and (6). However, considering the well‐known activity of MnO x for the chemical decomposition of H 2 O 2 ,21, 65, 66 one cannot rule out the alternative “disproportionation pathway” [i.e., the combination of Eqs. (6) and (7), sometimes referred in the literature27, 67 as the most plausible ORR mechanism], nor discard the possibility that both reaction mechanisms are simultaneously at play during the ORR mechanism on these materials.…”
Section: Resultsmentioning
confidence: 99%
“…The paper substrate is patterned with a catalyst along the microfluidic network for the generation of oxygen. When H 2 O 2 is injected through the microchannel network, it reaches the spot array and is decomposed by the catalyst, resulting in oxygen generation [26][27][28] . The substrate can also be patterned concurrently with other active materials, such as colorimetric or fluorescent inks to enable optical sensing of oxygen alongside delivery.…”
Section: Sensing and Delivery Mechanismsmentioning
confidence: 99%